Blau syndrome with a rare mutation in exon 9 of NOD2 gene - Jelena Velickovic; Fatma Silan; Firdevs Dincsoy Bir; Coskun Silan; Burcu Albuz; Ozturk Ozdemir (Taylor & Francis Group, 2019)
Blau syndrome is an autosomal dominant rare disease caused by mutations in NOD2 gene. Less than 200 patients published with Blau Syndrome Worldwide. We reported a 41-year old female Turkish patient diagnosed as Blau syndrome. Granulomatous dermatitis and severe headache, as well as recurrent chest and pelvic pain have been present since she was 8 years old. Arthritis started when she was teenage, hypertension diagnosed when she was 20 and other symptoms also occurred during the lifetime (severe preeclampsia, ischemic stroke, recurrent hemiparesis, recurrent-transient-vision-loss and renal-artery-stenosis). Genomic DNA was isolated from peripheral blood and 12 genes sequenced in Autoinflammatory panel on IonTorrent-S5-NGS platform with Parseq-VariFind™AIPassay. NGS analysis showed 107 variants in in the index case, mainly benign with no strong association with Blau syndrome. Additionally, we identified one very rare missense mutation in NOD2 gene (c2803G>A, p.Val935Met) and in silico assessment of the mutation indicated possible pathogenic significance and strong association with Blau syndrome. In addition, we analyzed family members of the index case and identified the same mutation in NOD2 gene. The segregation analysis shows the presence of the same mutant allele in NOD2 gene in the index case affected sister, as well as in her son with arthralgia, while in her non affecter brother we didn't detect the Val935Met mutation in NOD2 gene. Blau Syndrome is known as a very rare disease, mainly caused by mutations in NOD2 gene. Missense mutation diagnosed in our case could be responsible for the phenotype of the index case. Our results indicate the importance of NGS testing and its major role in the detection of rare mutations that may responsible for the onset of autoinflammatory disorders.